Conductive material, capacitor and preparation method thereof

The conductive material composition combined with reed slurry and nanocellulose is prepared by in-situ polymerization and casting molding, which solves the problems of poor combination and unstable conductivity in the prior art, and achieves efficient and stable conductivity and good mechanical properties, which is suitable for industrial applications.

CN120261173APending Publication Date: 2025-07-04CHINA NAT PULP & PAPER RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510413187.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-02
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

In the prior art, polypyrrole/fiber conductive materials have problems such as poor bonding, insufficient mechanical strength and flexibility, and unstable conductive properties during the preparation process, which makes it difficult to achieve industrialization, and the conductive active materials are easily lost.

Method used

The conductive material composition combined with reed slurry and nanocellulose is used to prepare the conductive material by in-situ polymerization method, and adhesive and conductive carbon materials are added, and regulators are added during the preparation process using the casting molding method to improve the conductivity and mechanical properties.

Benefits of technology

It realizes high efficiency, stability and uniformity of conductive materials, improves the mechanical strength and flexibility of the materials, is suitable for industrial production, avoids the loss of conductive active materials, and forms high-performance conductive materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of conductive materials, in particular to a conductive material, a capacitor and a preparation method of the capacitor. The conductive material is prepared from the following components in parts by weight: 2.1 to 54.6 parts of a polypyrrole / fiber composition, 9.8 to 79.0 parts of an adhesive, 0.03 to 2.1 parts of a surfactant, 2.1 to 54.6 parts of a conductive carbon material, 6.3 to 65.6 parts of a conditioning agent and 3 to 8 parts of water, the polypyrrole / fiber composition comprises pyrrole, ferric trichloride, reed pulp and nanocellulose, and the mass ratio of the pyrrole to the ferric trichloride to the reed pulp to the nanocellulose is (0.5-0.9): (2.4-4.4): 1: (0.05-0.15) according to the absolute dry fiber mass of the reed pulp. The conductive material obtained by adopting the technical scheme is easy to realize industrialization, high in conductive efficiency and good in mechanical property, and has important significance in promoting the development of a supercapacitor in the directions of flexibility, high performance, environmental protection, low cost and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of conductive materials, and specifically, to a conductive material, a capacitor, and a preparation method thereof. Background Art

[0002] With the development of Internet and artificial intelligence technologies, flexible wearable electronic devices have gradually penetrated into people's lives. In recent years, the market in this field has shown explosive growth. The booming development of flexible wearable devices has also put forward higher requirements for energy storage technologies, which need to be able to output stable electric energy under bending deformation conditions.

[0003] Supercapacitors are a kind of efficient and practical energy storage devices, which have the characteristics of high power density, long charge-discharge cycle life, fast charge-discharge, wide operating temperature range, etc. They have broad application prospects in flexible intelligent wearable electronic devices and have become a research hotspot at home and abroad.

[0004] Supercapacitors mainly consist of electrodes, current collectors, separators, electrolytes, and other auxiliary materials. Among them, the electrode is the key to achieving high performance and flexible functions of supercapacitors. Metals, carbon materials, and conductive polymers can all be used as conductive materials in electrodes.

[0005] Among them, polypyrrole is a typical conductive polymer, which has excellent electrical conductivity, optical properties, and biocompatibility. With the increasing attention of society to environmental protection, renewable cellulose has gradually become an ideal natural material to replace petroleum-based plastics for use in electronics, energy storage, and structural materials. Therefore, there are more and more studies on polypyrrole / fiber-based conductive electrode materials.

[0006] Polypyrrole / fiber conductive materials are usually prepared by methods such as wet forming of fibers followed by in-situ polymerization of pyrrole (or impregnation with polypyrrole) or in-situ polymerization of pyrrole on fibers followed by forming. In the forming-polymerization (or impregnation) method, the combination of polypyrrole and fibers is poor, and it is necessary to rely on multiple cycles of polymerization or impregnation to improve the electrical conductivity, making it difficult to industrialize; the conductive paper prepared by the in-situ polymerization-forming method has poor mechanical strength and flexibility due to the destruction of the bonding between fibers by polypyrrole, which is not conducive to processing and application. Moreover, these methods all have problems of limited pyrrole loading and uneven loading, resulting in unstable electrical conductivity. The electrical conductivity can be further improved by doping other conductive materials such as graphite and carbon nanotubes, but the addition by the wet method has problems such as easy loss of conductive active materials, and it is also not conducive to the strength performance of the materials.

[0007] In summary, there is an urgent need for a new type of conductive material in this field to solve the above technical problems.

[0008] In view of this, the present application is proposed. Summary of the Invention

[0009] The purpose of the present application is to provide a conductive material, a capacitor and a preparation method thereof, so as to solve at least one technical problem mentioned in the background art.

[0010] Specifically, in the first aspect of the present application, a conductive material is provided, comprising:

[0011] 2.1 - 54.6 parts of polypyrrole / fiber composition,

[0012] 9.8 - 79.0 parts of adhesive,

[0013] 0.03 - 2.1 parts of surfactant,

[0014] 2.1 - 54.6 parts of conductive carbon material,

[0015] 6.3 - 65.6 parts of regulator,

[0016] 3 - 8 parts of water,

[0017] Among them, the polypyrrole / fiber composition includes pyrrole, ferric chloride, reed pulp, and nanocellulose. Based on the absolute dry fiber mass of reed pulp, the mass ratio between pyrrole, ferric chloride, reed pulp, and nanocellulose is 0.5 - 0.9:2.4 - 4.4:1:0.05 - 0.15.

[0018] Adopting the above technical solution, since there is a certain amount of fines in reed pulp, cooperating with the high aspect ratio nanocellulose, it can increase the polymerization sites of pyrrole, which is beneficial to the growth and deposition of polypyrrole and improves the conductivity; at the same time, according to the research of the present application, the addition of nanocellulose also helps to improve the uniformity and strength performance of the conductive material. Therefore, by combining the above components, a conductive material with high conductive efficiency and good mechanical properties can be formed.

[0019] Preferably, the conductive material comprises:

[0020] 14.4 - 25.1 parts of polypyrrole / fiber composition,

[0021] 28.5 - 40.2 parts of adhesive,

[0022] 0.1 - 0.2 parts of surfactant,

[0023] 6.7 - 14.6 parts of conductive carbon material,

[0024] 25.9 - 33.5 parts of regulator,

[0025] 5 - 6 parts of water.

[0026] Preferably, based on the oven-dried fiber mass of reed pulp, the mass ratio of pyrrole, ferric chloride, reed pulp, and nanocellulose is 0.7 - 0.9: 3.4 - 4.4: 1: 0.05 - 0.15. More preferably, the mass ratio of pyrrole, ferric chloride, reed pulp, and nanocellulose is 0.7: 3.4: 1: 0.08.

[0027] Preferably, the basis weight of the conductive material is 100 - 300 g / m 2 .

[0028] Preferably, the thickness of the conductive material is 130 - 300 μm, the tensile strength is 3 - 20 N, the elongation at break is 3% - 40%, the softness value is 100 - 1500 mN, and the conductivity is 0.1 - 15.0 S / cm.

[0029] Preferably, the adhesive is composed of sodium carboxymethyl cellulose and an enhancing emulsion, and the enhancing emulsion is one or more of polyacrylate, styrene - acrylate, ethylene - vinyl acetate copolymer, and butadiene - styrene emulsion.

[0030] Preferably, the surfactant is sodium dodecylbenzenesulfonate.

[0031] Preferably, the conductive carbon material is selected from one or a combination of conductive carbon black and carbon nanotubes.

[0032] Preferably, the regulator includes one or a combination of wood powder, tobacco powder, and glycerol.

[0033] Preferably, the regulator is composed of wood powder and glycerol, or composed of tobacco powder and glycerol.

[0034] Preferably, the polypyrrole / fiber composition is prepared by the following method:

[0035] The reed pulp is treated at a beating degree of 40 - 80°SR, and the nanocellulose is mixed with the reed pulp. Pyrrole and ferric chloride are deposited on the surface of the mixed raw material of nanocellulose and reed pulp by in - situ polymerization through iron ion oxidation.

[0036] Preferably, the beating degree of the reed pulp is 50 - 78°SR.

[0037] In the second aspect of the present application, a capacitor is provided, and the capacitor material at least includes the conductive material as described in the first aspect of the present application.

[0038] In the third aspect of the present application, a preparation method of the conductive material as described in the first aspect of the present application is provided, and the method includes the steps:

[0039] Weigh each component according to the following ratio:

[0040] 0.5 - 5 parts of polypyrrole / fiber composition, 2 - 10 parts of adhesive, 0.01 - 0.1 part of surfactant, 0.5 - 5 parts of conductive carbon material, 1.5 - 6 parts of regulator, 80 - 95 parts of water. Among them, the polypyrrole / fiber composition includes pyrrole, ferric chloride, reed pulp, and nanocellulose. Based on the dry fiber mass of reed pulp, the mass ratio among pyrrole, ferric chloride, reed pulp, and nanocellulose is 0.5 - 0.9:2.4 - 4.4:1:0.05 - 0.15;

[0041] Preparation steps of polypyrrole / fiber composition: Treat reed pulp with beating degree of 40 - 80°SR, and mix nanocellulose with reed pulp. Pyrrole and ferric chloride are deposited on the surface of the mixed raw material of nanocellulose and reed pulp by in-situ polymerization through iron ion oxidation;

[0042] Preparation steps of conductive paste: First, mix the adhesive, conductive carbon material, and surfactant evenly, and after ultrasonic dispersion treatment, then add the polypyrrole / fiber composition, regulator, and water under stirring conditions and mix evenly;

[0043] Preparation steps of conductive material: Spread the above conductive paste, dry it, peel it off, roll it, and rewind it to obtain the conductive material.

[0044] Preferably, the deposition of pyrrole and ferric chloride on the surface of the mixed raw material of nanocellulose and reed pulp by in-situ polymerization through iron ion oxidation includes the steps:

[0045] Place the reed pulp slurry in a reaction device, place the reaction device in an ice-water bath, and sequentially add nanocellulose, ferric chloride, and pyrrole under stirring conditions. The stirring speed is 150 - 600 rpm, and the reaction time is 1 - 3 h, preferably 2 h.

[0046] Preferably, in the preparation steps of the conductive paste, the ultrasonic dispersion treatment includes the steps:

[0047] Treat with an ultrasonic cell disruptor, the treatment power is 500 W, ultrasonic treatment is carried out 100 - 500 times, the working time of each time is 2 s, and the interval time is 2 s.

[0048] Preferably, in the preparation steps of the conductive paste, the stirring conditions include:

[0049] The stirring speed is 400 - 1500 rpm, and the stirring time is 20 - 60 min.

[0050] Preferably, in the preparation steps of the conductive material, the spreading step includes spreading the conductive paste evenly on the surface of the running steel belt through a casting device.

[0051] Preferably, the beating degree of reed pulp is 50 - 78°SR.

[0052] Preferably, in the step of preparing the conductive material, the drying temperature is 80 - 150 °C. More preferably, the drying temperature is 90 - 100 °C.

[0053] Preferably, in the step of preparing the conductive material, the rolling pressure is 0.01 - 1 MPa. More preferably, the rolling pressure is 0.02 - 0.05 MPa.

[0054] In summary, the present application has the following beneficial effects:

[0055] 1. For the conductive material provided by the present application, since the reed pulp contains a certain amount of fine fibers, which cooperate with the nano-cellulose with a high aspect ratio, it can increase the polymerization sites of pyrrole, facilitate the growth and deposition of polypyrrole, and improve the conductivity; at the same time, according to the research of the present application, the addition of nano-cellulose also helps to improve the uniformity and strength performance of the conductive material. Therefore, by combining the above components, a conductive material with high conductive efficiency and good mechanical properties can be formed.

[0056] 2. For the conductive material provided by the present application, the casting forming method can avoid the loss of conductive active materials during the forming process by filtration, and all the effective components in the slurry can be retained; at the same time, it can prevent the coverage of the hydrogen bonds of fibers by a high amount of polypyrrole, which affects the material strength. The adhesive can endow the material with tensile properties and can be regulated, making the material have higher, more stable and more flexible conductive efficiency.

[0057] 3. The conductive material provided by the present application can be continuously produced and is easy to industrialize. The rolling after the conductive material is formed and dried can play a role in surface finishing, making the conductive material more uniform. Specific Embodiments

[0058] The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present application. On the contrary, they are merely examples of devices and methods consistent with some aspects of the present application as detailed in the appended claims.

[0059] The terms used in the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The singular forms of "a", "the" and "said" used in the present application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more of the associated listed items.

[0060] The present application will be described in detail below through embodiments.

[0061] Polypyrrole / fiber conductive materials are usually prepared by wet forming of fibers followed by in-situ polymerization of pyrrole (or impregnation with polypyrrole) or by first in-situ polymerizing pyrrole on the fibers and then forming. In the forming-polymerization (or impregnation) method, the combination of polypyrrole and fibers is poor, and multiple cycles of polymerization or impregnation are required to improve the conductivity, making it difficult to industrialize. For the conductive paper prepared by the in-situ polymerization-forming method, since polypyrrole destroys the bonding between fibers, the mechanical strength and flexibility of the conductive paper are poor, which is not conducive to processing and application. Moreover, these methods all have the problems of limited pyrrole loading and uneven loading, resulting in unstable conductivity. The conductivity can be further improved by doping other conductive materials such as graphite and carbon nanotubes. However, when using the wet-making method to add, there are problems such as easy loss of conductive active materials, and it is also not conducive to the strength performance of the materials.

[0062] In view of this, to solve the technical problems existing in the background technology, the inventive concept of this application is to provide a conductive material, including: 2.1 - 54.6 parts of polypyrrole / fiber composition, 9.8 - 79.0 parts of adhesive, 0.03 - 2.1 parts of surfactant, 2.1 - 54.6 parts of conductive carbon material, 6.3 - 65.6 parts of regulator, and 3 - 8 parts of water. Among them, the polypyrrole / fiber composition includes pyrrole, ferric chloride, reed pulp, and nanocellulose. Taking the absolute dry fiber of reed pulp as a reference, the mass ratio between pyrrole, ferric chloride, reed pulp, and nanocellulose is 0.5 - 0.9:2.4 - 4.4:1:0.05 - 0.15.

[0063] According to this inventive concept, since reed pulp contains a certain amount of fines, which cooperate with the high aspect ratio nanocellulose, it can increase the sites for pyrrole polymerization, be conducive to the growth and deposition of polypyrrole, and improve the conductivity. At the same time, according to the research of this application, the addition of nanocellulose also helps to improve the uniformity and strength performance of the conductive material. Therefore, by combining the above components, a conductive material with high conductive efficiency and good mechanical properties can be formed.

[0064] To better understand the above technical solution, the following will describe the above technical solution in detail in combination with specific embodiments. Those skilled in the art should also understand that the reaction time and component feeding involved in this application cannot be absolutely accurate in the actual production process, but are within the allowable error range. For example, if it is desired to heat the sample for 30 minutes, the actual operation may be 1 second more or less than 30 minutes; if it is desired to weigh 30 g of the sample, the actual weight may be 30.001 g or 29.998 g.

[0065] Unless otherwise specified, all raw materials involved in this application are commercially available products.

[0066] Experimental Example 1

[0067] Unless otherwise specified, the parameters in this application are detected using existing technologies:

[0068] The viscosity of the conductive paste is measured using a rotational viscometer;

[0069] Referring to the relevant paper standards GB / T 451.2-2023, GB / T 451.3-2002, GB / T 12914-2018, GB / T 8942-2016, GB / T 462-2023, the basis weight, thickness, tensile strength and elongation, softness value, and moisture content of the conductive material are measured;

[0070] The conductivity of the conductive material is measured using the four-probe method.

[0071] Example 1

[0072] Preparation of polypyrrole / fiber composition: The beating degree of reed pulp is 60°SR, the dosage of nanocellulose relative to the absolute dry fiber of reed pulp is 8%, the dosage of pyrrole relative to the absolute dry fiber of reed pulp is 70%, the molar ratio of ferric chloride to pyrrole is 2:1, and pyrrole is deposited on the surface of the mixed raw material of fiber and nanocellulose by in-situ polymerization through the oxidation of ferric ions in ferric chloride to form polypyrrole / fiber slurry. Among them, the deposition of pyrrole on the surface of the mixed raw material of fiber and nanocellulose by in-situ polymerization through the oxidation of ferric ions in ferric chloride includes the steps of: placing the reed pulp in a reaction device, placing the reaction device in an ice-water bath, and sequentially adding nanocellulose, ferric chloride, and pyrrole under stirring conditions, with a stirring speed of 600 rpm and a reaction time of 1 h.

[0073] Preparation of conductive paste: The mass fraction of polypyrrole / fiber slurry in the conductive paste is 2%; the adhesive is composed of sodium carboxymethylcellulose and polyacrylate emulsion, the mass fraction of sodium carboxymethylcellulose in the conductive paste is 2.5%, and the mass fraction of polyacrylate emulsion in the conductive paste is 1%; the mass fraction of the surfactant sodium dodecylbenzenesulfonate in the conductive paste is 0.02%; the conductive carbon materials are conductive carbon black and carbon nanotubes, the mass fraction of conductive carbon black in the conductive paste is 0.7%, and the mass fraction of carbon nanotubes in the conductive paste is 0.6%; the regulator includes tobacco powder with a mesh size of 140, with a mass fraction of 0.8% in the conductive paste, and glycerol, with a mass fraction of 2% in the conductive paste; the mass fraction of water in the conductive paste is 90.38%; when preparing the conductive paste, first mix the adhesive with the conductive carbon materials and the surfactant evenly, and after ultrasonic dispersion treatment, then add the polypyrrole / fiber slurry, the regulator, and water under stirring conditions and mix evenly. Among them, the ultrasonic dispersion treatment includes the steps of: treating with an ultrasonic cell disruptor, with a treatment power of 500 W, ultrasonic treatment for 100 times, with a working time of 2 s each time and an interval time of 2 s; the stirring conditions include: a stirring speed of 400 rpm and a stirring time of 60 min.

[0074] Preparation of conductive material: The above conductive paste is evenly spread on the surface of a running steel belt through a casting device, and then dried with hot air, peeled, roll-pressed, and rewound to obtain a conductive material. The drying temperature is 100°C, and the roll-pressing pressure is 0.05 MPa.

[0075] The viscosity of the prepared conductive paste is 2839 cP;

[0076] The basis weight of the conductive material is 150 g / m 2 , the thickness is 214 μm, the tensile strength is 4.6 N, the elongation at break is 10.6%, the softness value is 448 mN, the conductivity is 3.5 S / cm, and the moisture content is 6%;

[0077] Among them, the conductive material contains: 19.5 parts of polypyrrole / fiber composition, 34.2 parts of adhesive, 0.20 parts of surfactant, 12.7 parts of conductive carbon material, 27.4 parts of regulator, and 6 parts of water.

[0078] Example 2

[0079] Preparation of polypyrrole / fiber composition: The beating degree of reed pulp is 60°SR, the dosage of nanocellulose relative to the absolutely dry fiber is 8%, the dosage of pyrrole relative to the absolutely dry fiber is 90%, and the molar ratio of ferric chloride to pyrrole is 2:1. Pyrrole is deposited on the surface of the mixed raw material of fiber and nanocellulose by in-situ polymerization through the oxidation of ferric ions in ferric chloride to form a polypyrrole / fiber slurry. Among them, the deposition of pyrrole on the surface of the mixed raw material of fiber and nanocellulose by in-situ polymerization through the oxidation of ferric ions in ferric chloride includes the steps of: placing the reed pulp in a reaction device, placing the reaction device in an ice-water bath, and sequentially adding nanocellulose, ferric chloride, and pyrrole under stirring conditions, with a stirring speed of 300 rpm and a reaction time of 2 h.

[0080] Preparation of Conductive Paste: The mass fraction of polypyrrole / fiber paste in the conductive paste is 2%; the adhesive is composed of sodium carboxymethyl cellulose and polyacrylate latex. The mass fraction of sodium carboxymethyl cellulose in the conductive paste is 3%, and the mass fraction of polyacrylate emulsion in the conductive paste is 0.7%; the mass fraction of sodium dodecylbenzenesulfonate in the conductive paste is 0.02%; the conductive carbon materials are conductive carbon black and carbon nanotubes. The mass fraction of conductive carbon black in the conductive paste is 0.7%, and the mass fraction of carbon nanotubes in the conductive paste is 0.9%; the regulator includes tobacco powder with a mesh size of 140, with a mass fraction of 1% in the conductive paste, and glycerol, with a mass fraction of 2% in the conductive paste; the mass fraction of water in the conductive paste is 89.68%. When preparing the conductive paste, first mix the adhesive, conductive carbon materials, and surfactant evenly, and after ultrasonic dispersion treatment, then add the polypyrrole / fiber paste, regulator, and water under stirring conditions and mix evenly. Among them, the ultrasonic dispersion treatment includes the steps: treating with an ultrasonic cell disruptor, with a treatment power of 500 W, ultrasonic treatment for 300 times, with a working time of 2 s each time and an interval time of 2 s; the stirring conditions include: a stirring speed of 1000 rpm and a stirring time of 30 min.

[0081] Preparation of Conductive Material: The above-mentioned conductive paste is evenly spread on the surface of a running steel belt through a casting device, and then dried with hot air, peeled, roll-pressed, and rewound to obtain the conductive material. The drying temperature is 100 °C, and the roll-pressing pressure is 0.05 MPa.

[0082] The viscosity of the prepared conductive paste is 3459 cP, the basis weight of the conductive material is 180 g / m 2 , the thickness is 237 μm, the tensile strength is 8.7 N, the elongation at break is 15.4%, the softness value is 590 mN, the conductivity is 9.1 S / cm, and the moisture content is 6%.

[0083] Among them, the conductive material contains: 18.2 parts of polypyrrole / fiber composition, 33.7 parts of adhesive, 0.18 part of surfactant, 14.6 parts of conductive carbon materials, 27.3 parts of regulator, and 6 parts of water.

[0084] Example 3

[0085] Preparation of polypyrrole / fiber composition: The beating degree of reed pulp is 78°SR, the dosage of nanocellulose is 5% relative to the absolutely dry fiber, the dosage of pyrrole is 80% relative to the absolutely dry fiber, the molar ratio of ferric chloride to pyrrole is 2:1, and pyrrole is deposited on the surface of the mixed raw materials of fiber and nanocellulose by in-situ polymerization through the oxidation of ferric ions in ferric chloride to form polypyrrole / fiber slurry. Among them, the deposition of pyrrole on the surface of the mixed raw materials of fiber and nanocellulose by in-situ polymerization through the oxidation of ferric ions in ferric chloride includes the steps of: placing the reed slurry in a reaction device, placing the reaction device in an ice-water bath, and sequentially adding nanocellulose, ferric chloride and pyrrole under stirring conditions, with a stirring speed of 150 rpm and a reaction time of 3 h.

[0086] Preparation of conductive slurry: The mass fraction of polypyrrole / fiber slurry in the conductive slurry is 3%; the adhesive is composed of sodium carboxymethylcellulose and ethylene-vinyl acetate copolymer, the mass fraction of sodium carboxymethylcellulose in the conductive slurry is 2.4%, and the mass fraction of ethylene-vinyl acetate copolymer emulsion in the conductive slurry is 1%; the mass fraction of sodium dodecylbenzenesulfonate in the conductive slurry is 0.02%; the conductive carbon material is conductive carbon black, and the mass fraction of conductive carbon black in the conductive slurry is 0.8%; the regulator includes tobacco powder with a mesh size of 140, and the mass fraction in the conductive slurry is 1.5%, and glycerol, and the mass fraction in the conductive slurry is 2.5%; the mass fraction of water in the conductive slurry is 88.78%. When preparing the conductive slurry, first mix the adhesive with the conductive carbon material and surfactant evenly, and after ultrasonic dispersion treatment, then add the polypyrrole / fiber slurry, regulator and water under stirring conditions and mix evenly. Among them, the ultrasonic dispersion treatment includes the steps of: treating with an ultrasonic cell crusher, with a treatment power of 500 W, ultrasonic treatment for 500 times, with a working time of 2 s each time and an interval time of 2 s; the stirring conditions include: a stirring speed of 1500 rpm and a stirring time of 20 min.

[0087] Preparation of conductive material: The above-mentioned conductive slurry is evenly spread on the surface of a running steel belt through a casting device, and then dried with hot air, peeled, rolled and rewound to obtain a conductive material, with a drying temperature of 90°C and a rolling pressure of 0.05 MPa.

[0088] The viscosity of the prepared conductive slurry is 3179 cP, the basis weight of the conductive material is 185 g / m 2 , the thickness is 201 μm, the tensile strength is 8.0 N, the elongation at break is 18.3%, the softness value is 561 mN, the conductivity is 1.8 S / cm, and the moisture content is 6%.

[0089] Among them, the conductive material contains: 25.1 parts of polypyrrole / fiber composition, 28.5 parts of adhesive, 0.17 parts of surfactant, 6.7 parts of conductive carbon material, 33.5 parts of regulator, and 6 parts of water.

[0090] Example 4

[0091] Preparation of polypyrrole / fiber composition: The beating degree of reed pulp is 50°SR, the dosage of nanocellulose is 15% relative to the absolutely dry fiber, the dosage of pyrrole is 70% relative to the absolutely dry fiber, the molar ratio of ferric chloride to pyrrole is 2:1, and pyrrole is deposited on the surface of the mixed raw material of fiber and nanocellulose by in-situ polymerization through the oxidation of ferric ions in ferric chloride to form polypyrrole / fiber slurry. Among them, the deposition of pyrrole on the surface of the mixed raw material of fiber and nanocellulose by in-situ polymerization through the oxidation of ferric ions in ferric chloride includes the steps of: placing the reed slurry in a reaction device, placing the reaction device in an ice-water bath, and sequentially adding nanocellulose, ferric chloride and pyrrole under stirring conditions, with a stirring speed of 300 rpm and a reaction time of 2 h.

[0092] Preparation of conductive slurry: The mass fraction of polypyrrole / fiber slurry in the conductive slurry is 1.5%; the adhesive is composed of sodium carboxymethylcellulose and ethylene-vinyl acetate copolymer, the mass fraction of sodium carboxymethylcellulose in the conductive slurry is 2.2%, and the mass fraction of ethylene-vinyl acetate copolymer emulsion in the conductive slurry is 2%; the mass fraction of sodium dodecylbenzenesulfonate in the conductive slurry is 0.01%; the conductive carbon materials are conductive carbon black and carbon nanotubes, the mass fraction of conductive carbon black in the conductive slurry is 0.7%, and the mass fraction of carbon nanotubes in the conductive slurry is 0.8%; the viscosity regulator is 200-mesh wood powder, with a mass fraction of 1% in the conductive slurry, and glycerol, with a mass fraction of 1.7% in the conductive slurry; the mass fraction of water in the conductive slurry is 90.09%. When preparing the conductive slurry, first mix the adhesive with the conductive carbon material and surfactant evenly, and after ultrasonic dispersion treatment, then add the polypyrrole / fiber slurry, regulator and water under stirring conditions and mix evenly. Among them, the ultrasonic dispersion treatment includes the steps of: treating with an ultrasonic cell disruptor, with a treatment power of 500 W, ultrasonic treatment for 300 times, with a working time of 2 s each time and an interval time of 2 s; the stirring conditions include: a stirring speed of 1200 rpm and a stirring time of 30 min.

[0093] Preparation of conductive material: The above-mentioned conductive slurry is evenly spread on the surface of the running steel belt through a casting device, and then dried with hot air, peeled, rolled and rewound to obtain a conductive material, with a drying temperature of 100 °C and a rolling pressure of 0.02 MPa.

[0094] The viscosity of the prepared conductive slurry is 2689 cP, the basis weight of the conductive material is 253 g / m 2 , the thickness is 266 μm, the tensile strength is 12.4 N, the elongation at break is 28.9%, the softness value is 1267 mN, the conductivity is 5.7 S / cm, and the moisture content is 5%.

[0095] Among them, the conductive material contains: 14.4 parts of polypyrrole / fiber composition, 40.2 parts of adhesive, 0.10 part of surfactant, 14.4 parts of conductive carbon material, 25.9 parts of regulator, and 5 parts of water.

[0096] Comparative Example 1

[0097] The same polypyrrole / fiber slurry and conductive material preparation process as in Example 1 were adopted. The difference is that the conductive slurry in this example does not contain a viscosity regulator, and other components are the same as those in Example 1. The specific preparation method is as follows:

[0098] Preparation of polypyrrole / fiber composition: The beating degree of reed pulp is 60°SR, the dosage of nanocellulose relative to absolute dry fiber is 8%, the dosage of pyrrole relative to absolute dry fiber is 70%, the molar ratio of ferric chloride to pyrrole is 2:1, and pyrrole is deposited on the surface of the mixed raw material of fiber and nanocellulose by in-situ polymerization through the oxidation of ferric ions in ferric chloride to form polypyrrole / fiber slurry. Among them, the deposition of pyrrole on the surface of the mixed raw material of fiber and nanocellulose by in-situ polymerization through the oxidation of ferric ions in ferric chloride includes the steps of: placing the reed pulp in a reaction device, placing the reaction device in an ice-water bath, and sequentially adding nanocellulose, ferric chloride, and pyrrole under stirring conditions, with a stirring speed of 300 rpm and a reaction time of 2 h.

[0099] Preparation of conductive slurry: The mass fraction of polypyrrole / fiber slurry in the conductive slurry is 2%; the adhesive consists of sodium carboxymethylcellulose and polyacrylate emulsion. The mass fraction of sodium carboxymethylcellulose in the conductive slurry is 2.5%, and the mass fraction of polyacrylate emulsion in the conductive slurry is 1%; the mass fraction of sodium dodecylbenzenesulfonate in the conductive slurry is 0.02%; the conductive carbon material is conductive carbon black and carbon nanotubes. The mass fraction of conductive carbon black in the conductive slurry is 0.7%, and the mass fraction of carbon nanotubes in the conductive slurry is 0.6%; the mass fraction of plasticizer glycerol in the conductive slurry is 2%; the mass fraction of water in the conductive slurry is 91.28%. When preparing the conductive slurry, first mix the adhesive, conductive carbon material, and surfactant evenly, and after ultrasonic dispersion treatment, then add the polypyrrole / fiber slurry, regulator, and water under stirring conditions and mix evenly. Among them, the ultrasonic dispersion treatment includes the steps of: treating with an ultrasonic cell disruptor, with a treatment power of 500 W, ultrasonic treatment for 300 times, with a working time of 2 s each time and an interval time of 2 s; the stirring conditions include: a stirring speed of 1000 rpm and a stirring time of 30 min.

[0100] Preparation of conductive material: The above-mentioned conductive slurry is evenly spread on the surface of a running steel belt through a casting device, and then dried with hot air, peeled, rolled, and rewound to obtain a conductive material. The drying temperature is 100°C, and the rolling pressure is 0.05 MPa.

[0101] The conductive paste flows onto the surface of the steel belt through a casting device. It is observed that the paste at the edge of the steel belt significantly shrinks inward, and the adhesion of the paste to the surface of the steel belt is poor. After drying, the width of the conductive material decreases and the edge is irregular, resulting in an increase in basis weight, thickness, and difficulty in regulation. The basis weight of the prepared conductive material is 194 g / m 2 , far deviating from the preset 150 g / m 2 , and the width of the material deviates by at least 1 cm, making it difficult to precisely regulate parameters such as the basis weight, width, and thickness of the final material in actual production.

[0102] Comparative Example 2

[0103] Preparation of polypyrrole / fiber composition: The beating degree of reed pulp is 60°SR, the dosage of nanocellulose relative to oven-dry fiber is 8%, the dosage of pyrrole relative to oven-dry fiber is 90%, the molar ratio of ferric chloride to pyrrole is 2:1, and pyrrole is deposited on the surface of the mixed raw material of fiber and nanocellulose by in-situ polymerization through the oxidation of ferric ions in ferric chloride to form polypyrrole / fiber slurry. Among them, the deposition of pyrrole on the surface of the mixed raw material of fiber and nanocellulose by in-situ polymerization through the oxidation of ferric ions in ferric chloride includes the steps of: placing the reed pulp in a reaction device, placing the reaction device in an ice-water bath, and sequentially adding nanocellulose, ferric chloride, and pyrrole under stirring conditions, with a stirring speed of 300 rpm and a reaction time of 2 h.

[0104] Preparation of conductive material: The above-mentioned polypyrrole / fiber slurry is defibrated using a pulp standard defibrator, dehydrated and formed using a rapid sheet former, pressed at 300 Mpa for 1 min, and dried using a drying cylinder at 100 °C to obtain the conductive material.

[0105] The basis weight of the prepared conductive material is 178 g / m 2 , the thickness is 373 μm, the tensile strength is 4.8 N, the elongation at break is 3.58%, the softness value > 2000 mN, the conductivity is 9.3 S / cm, and the moisture content is 6%.

[0106] Compared with Example 2, Comparative Example 2 uses in-situ polymerization of pyrrole - wet forming to prepare the conductive material, and the polypyrrole / fiber slurry used is the same as that in Example 2. Compared with the conductive material prepared in Example 2, the conductivity of the comparative example is similar, both being 9.0 - 9.5 S / cm. The tensile strength and elongation at break of Example 2 are significantly higher than those of Comparative Example 2, and the softness value (the lower the softness value, the softer the material) is lower than that of Comparative Example 2, indicating that the strength performance and flexible characteristics of the conductive material prepared by the present invention are better at similar conductivities.

[0107] According to the research of this application, the applicant found that for the conductive material containing polypyrrole / plant fiber, by using the casting forming method of this application, the loss of conductive active materials during the filtration forming process can be avoided, and all the effective components in the slurry can be retained. At the same time, when the amount of polypyrrole is relatively high, it can prevent the coverage of hydrogen bonds of fibers and affect the material strength. The adhesive can endow the material with tensile properties and can be regulated, making the material have higher, more stable, and more flexible conductivity. In addition, the method of the present invention can be continuously produced and is easy to industrialize. The rolling of the formed and dried conductive material can play a role in surface finishing, making the conductive material more uniform.

[0108] Furthermore, pyrrole is in-situ polymerized on the surface of hybrid fibers containing microfibrillated cellulose (MFC). The plant fiber in the hybrid fibers is reed pulp. Since reed pulp contains a certain amount of fines, cooperating with the nano-cellulose with a high aspect ratio, it can increase the polymerization sites of pyrrole, facilitate the growth and deposition of polypyrrole, and improve the conductivity. At the same time, nano-cellulose helps to improve the viscosity stability of the conductive slurry, the uniformity of the conductive film, and the strength performance.

[0109] Finally, wood powder or tobacco powder is used as a viscosity regulator in the conductive slurry. It can not only adjust the viscosity of the slurry but also adjust the affinity between the slurry and the steel belt during forming, which is beneficial to the spreading and forming of the slurry on the surface of the steel plate.

[0110] In summary, the conductive material, capacitor, and their preparation methods provided by this application can easily achieve industrialization, have high conductivity, and good mechanical properties, which are of great significance for promoting the development of supercapacitors in the directions of flexibility, high performance, environmental friendliness, and low cost.

[0111] It should be noted that for those of ordinary skill in the art, the technical features in the above embodiments can be freely combined, and the formed technical solutions also belong to the embodiments disclosed in this application.

[0112] Furthermore, without departing from the principle of this application, several improvements and modifications can be made to this application, and these improvements and modifications also fall within the protection scope of the claims of this application.

Claims

1. A conductive material, characterized in that, Comprising: 2.1 - 54.6 parts of polypyrrole / fiber composition, 9.8 - 79.0 parts of adhesive, 0.03 - 2.1 parts of surfactant, 2.1 - 54.6 parts of conductive carbon material, 6.3 - 65.6 parts of regulator, 3 - 8 parts of water, Among them, the polypyrrole / fiber composition includes pyrrole, ferric chloride, reed pulp, and nanocellulose. Based on the dry fiber mass of reed pulp, the mass ratio between pyrrole, ferric chloride, reed pulp, and nanocellulose is 0.5 - 0.9:2.4 - 4.4:1:0.05 - 0.

15.

2. The conductive material according to claim 1, wherein: The conductive material includes: 14.4 - 25.1 parts of polypyrrole / fiber composition, 28.5 - 40.2 parts of adhesive, 0.1 - 0.2 parts of surfactant, 6.7 - 14.6 parts of conductive carbon material, 25.9 - 33.5 parts of regulator, 5 - 6 parts of water.

3. The conductive material according to claim 1, characterized in that: Based on the dry fiber mass of reed pulp, the mass ratio between pyrrole, ferric chloride, reed pulp, and nanocellulose is 0.7 - 0.9:3.4 - 4.4:1:0.05 - 0.

15.

4. The conductive material according to claim 1, wherein: The quantitative amount of the conductive material is 100 - 300 g / m 2 .

5. The conductive material according to claim 1, wherein: The thickness of the conductive material is 130 - 300 μm, the tensile strength is 3 - 20 N, the elongation at break is 3% - 40%, the softness value is 100 - 1500 mN, and the conductivity is 0.1 - 15.0 S / cm.

6. The conductive material according to claim 1, characterized in that: The adhesive consists of sodium carboxymethyl cellulose and an enhancing emulsion. The enhancing emulsion is one or more of polyacrylate, styrene - acrylate, ethylene - vinyl acetate copolymer, and butadiene - styrene emulsion, and / or the surfactant is sodium dodecylbenzenesulfonate, and / or the conductive carbon material is selected from one or a combination of conductive carbon black and carbon nanotubes, and / or the regulator includes a combination of one or several of wood powder, tobacco powder, and glycerol.

7. The conductive material according to claim 6, characterized in that: The regulator consists of wood powder and glycerol, or consists of tobacco powder and glycerol.

8. The conductive material according to any one of claims 1-7, characterized in that: The polypyrrole / fiber composition is prepared by the following method: The reed pulp is treated at a beating degree of 40 - 80°SR, and the nanocellulose is mixed with the reed pulp. Pyrrole and ferric chloride are deposited on the surface of the mixed raw material of nanocellulose and reed pulp by in - situ polymerization through iron ion oxidation.

9. A capacitor, characterized in that, The capacitor material includes at least the conductive material as described in any one of claims 1 - 8.

10. A method for preparing the conductive material as described in any one of claims 1 - 8, the method comprising the steps: Weigh each component according to the following ratio: 0.5 - 5 parts of polypyrrole / fiber composition, 2 - 10 parts of adhesive, 0.01 - 0.1 part of surfactant, 0.5 - 5 parts of conductive carbon material, 1.5 - 6 parts of regulator, 80 - 95 parts of water, wherein, The polypyrrole / fiber composition includes pyrrole, ferric chloride, reed pulp, and nanocellulose. Based on the dry fiber mass of reed pulp, the mass ratio between pyrrole, ferric chloride, reed pulp, and nanocellulose is 0.5 - 0.9:2.4 - 4.4:1:0.05 - 0.15; Steps for preparing the polypyrrole / fiber composition: The reed pulp is beaten to a beating degree of 40 - 80°SR, and the nanocellulose is mixed with the reed pulp. Pyrrole and ferric chloride are deposited on the surface of the mixed raw material of nanocellulose and reed pulp by in - situ polymerization through iron ion oxidation; Steps for preparing the conductive paste: First, uniformly mix the adhesive, conductive carbon material, and surfactant. After ultrasonic dispersion treatment, add the polypyrrole / fiber composition, regulator, and water under stirring conditions, and mix uniformly to make its viscosity 2000 - 6000 cP; Steps for preparing the conductive material: Prepare the conductive material by spreading, drying, peeling, rolling, and rewinding the above conductive paste.